Talus Bipartitus: A Rare Anatomical Variant Presenting as an Entrapment Neuropathy of the Tibial Nerve within the Tarsal Tunnel - M. O. Abrego; F. L. De Cicco; N. E. Gimenez; M. O. Marquesini; P. Sotelano; M. N. Carrasco; M. G. Santini Araujo (Case Reports in Orthopedics)
Tarsal tunnel syndrome is an entrapment neuropathy of the tibial nerve within the tarsal tunnel that lies beneath the retinaculum on the medial side of the ankle. It is often underdiagnosed. Talus bipartitus is a rare anatomical variant; only a few cases have been described in medical literature. We report a case of a 36-year-old female with tarsal tunnel syndrome secondary to a talus bipartitus undergoing surgical treatment with good clinical outcome. To our knowledge, talus bipartitus presenting as tarsal tunnel syndrome has no previous reports. Image studies and physical examination are crucial to reach precise diagnosis.